2015
DOI: 10.1016/j.mayocp.2015.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Uric Acid: A Missing Link Between Hypertensive Pregnancy Disorders and Future Cardiovascular Disease?

Abstract: Objective To determine whether women who had a hypertensive pregnancy disorder (HPD) have elevated uric acid concentrations decades after pregnancy, when compared to women who had normotensive pregnancies. Patients and Methods The Genetic Epidemiology Network of Arteriopathy study measured uric acid concentrations in Hispanic (30%), non-Hispanic white (28%), and non-Hispanic black (42%) women (60 ± 10 years of age). This cross-sectional study was conducted between July 1, 2000 and December 31, 2004. Hispanic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 40 publications
2
8
0
Order By: Relevance
“…Our data are also consistent to a certain extent with the data resulting from several previous studies [23,31,40], where significantly higher serum levels of uric acid were found in patients with a prior exposure to hypertensive pregnancy disorders or PE only. Hyperuricemia is associated with cardiovascular disease risk factors and cardiovascular diseases, often being a predictor of incident events [41,42,43].…”
Section: Discussionsupporting
confidence: 93%
“…Our data are also consistent to a certain extent with the data resulting from several previous studies [23,31,40], where significantly higher serum levels of uric acid were found in patients with a prior exposure to hypertensive pregnancy disorders or PE only. Hyperuricemia is associated with cardiovascular disease risk factors and cardiovascular diseases, often being a predictor of incident events [41,42,43].…”
Section: Discussionsupporting
confidence: 93%
“…This model shows that the group characterized by overweight and hyperglycemia has 4 times increased risk of UA higher than 4 mg/dL, but after adding serum triglycerides risk augments 7 times. In the literature, high serum concentration of UA is considered as a risk factor of CVDs or metabolic disorders; however, higher concentrations of this parameter have been considered [37, 37, 38]. Thus, overweight women with hyperglycemia and hypertriglyceridemia have a higher chance of increasing UA level.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperuricemia and gout are increasing worldwide and are affecting 1 to 2% of the adult population [ 72 – 74 ]. Hyperuricemia is also associated with atrial stiffness, cardiovascular diseases, and hypertensive pregnancy disorders [ 75 , 76 ], and can be controlled by medication and change in lifestyle and eating habits [ 30 , 31 , 77 ]. Majority of the popular and energy-rich food items contain moderate to high purine content [ 77 ].…”
Section: Discussionmentioning
confidence: 99%